2012
DOI: 10.1007/s12011-012-9480-z
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Influences of TiO2 Nanoparticles on Barley (Hordeum vulgare L.) Tissue Culture

Abstract: In the last decades, extensive research on the effects of nano-TiO₂ on plant systems and different microorganisms has confirmed its photocatalytic and antimicrobial activity. However, there is no report on its application in plant cell and tissue culture as well as its role in eliminating contaminating microorganisms in tissue culture. In this work, barley mature embryos were cultured in Murashige and Skoog medium with four concentrations (0, 10, 30, 60 μg/ml) of TiO₂ suspension in four repetitions. Quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 31 publications
3
27
0
1
Order By: Relevance
“…This finding supports our previous research which showed that foliar application of nTiO 2 on barley plants in a semi-arid region positively affected growth rate and seed yield (Janmohammadi et al, 2016a). It seems that, nTiO 2 plays a significant role in activatingdefense mechanism and modulating biosynthesis of phytohormones such as cytokinins and gibberellin (Mandeh et al, 2012). However, the accumulation of the nano-particles in plant tissue can be very important point from food safety perspective, therefore; their measurement in future experiments can be very valuable and provide precious information.…”
Section: Discussionsupporting
confidence: 91%
“…This finding supports our previous research which showed that foliar application of nTiO 2 on barley plants in a semi-arid region positively affected growth rate and seed yield (Janmohammadi et al, 2016a). It seems that, nTiO 2 plays a significant role in activatingdefense mechanism and modulating biosynthesis of phytohormones such as cytokinins and gibberellin (Mandeh et al, 2012). However, the accumulation of the nano-particles in plant tissue can be very important point from food safety perspective, therefore; their measurement in future experiments can be very valuable and provide precious information.…”
Section: Discussionsupporting
confidence: 91%
“…However evidence from this study suggested that nTiO 2 along with nano-fertilizers can effectively influence both vegetative and reproductive characteristics under supplemental irrigation in semi-arid region. It appears that nTiO 2 may play a significant role in activation of defense mechanism and modulating the biosynthesis of phytohormones such as cytokinins and gibberellin (Mandeh et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that these nanocomposites were safe for wheat seed germination, emergence and growth of seedlings and they can provide a regulated, responsive and on time delivery of nutrients to plants. Also several studies show that exogenous application of some nanoparticle can significantly improve plant growth (Mandeh et al, 2012;Song et al, 2013). Titanium dioxide nanoparticles (nTiO 2 ) are promising as efficient nutrient source for plants to improve biomass production due to enhanced the nitrogen assimilation, photoreduction activities of photosystem II and electron transport chain, scavenging of reactive oxygen species, and (Morteza et al, 2013;Raliya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cells growth increase under nitrogen might be a reason for plant height rise [27]. Several studies indicated that exogenous application of some nanoparticles can significantly improve plant growth [28] [29]. Previous studies reported that applying 3.0 L·ha −1 doses of Nanonat and Ferbanat has promoted tomatoes' yield and plant growth [30].…”
Section: Plant Height and Panicle Lengthmentioning
confidence: 99%